Peranan Guru dalam Implementasi Kurikulum 2013 di Madrasah Ibtidaiyah Negeri 1 Jombang - Abdul Rouf; Raghda Lufita (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to find out how the role of teachers in the implementation of the Curriculum 2013, what are the inhibiting factors for teachers in curriculum implementation at MIN 1 Jombang. This study included qualitative descriptive research. In collecting the data, the author uses the method of observation, interviews and documentation. While for the analysis the author uses data reduction, data presentation, draw conclusions. The results of this study are that the Implementation of the Curriculum 2013 at MIN 1 Jombang in general has gone well starting from the preparation stage to the evaluation phase. Because from the beginning of the appointment of MIN 1 Jombang as the only school at the SD / MI level that uses Curriculum 2013 in Jombang, there is always assistance from the Government regarding the procedures for implementing the Curriculum 2013. Therefore, the school held an enrichment as a form of adding material for class VI students to be better prepared to face the National Examination. Because in Jombang the implementation of the National Exams at the elementary / MI level still uses the KTSP curriculum system.